Science capital: Results from a Finnish population survey - Kaakinen, Johanna K.; Havu-Nuutinen, Sari; Häikiö, Tuomo; Julku, Hanna; Koskela, Teija; Mikkilä-Erdmann, Mirjamaija; Pihlajamäki, Milla; Pritup, Daria; Pulkkinen, Kirsi; Saarikivi, Katri; Simola, Jaana; Wikström, Valtteri (SAGE Publications, 2025)
This study examined science capital among Finnish adults (N = 1572), who responded to 37 survey items assessing science capital. Factor analysis suggested four science capital dimensions: visiting science-related places, science attitudes, science-related self-efficacy, and early support for studying natural sciences. Higher education and higher parental education were linked to higher science capital across all dimensions. Older participants exhibited lower science-related self-efficacy, less early support, and more negative science attitudes than younger respondents. Age and education were stronger predictors of science-related self-efficacy and early encouragement for men than women, and mothers’ education had a weaker effect on science-related self-efficacy for men. The results show that science capital is a multidimensional construct and highlights that younger generations in Finland have had more opportunities to develop their science capital. These findings emphasize the need for early and equitable support to foster positive science attitudes and participation.